Incorporando o trabalho técnico social (TTS) nas estratégias de comunicação elaboradas pelas relações públicas - (:unkn) unknown (Universidade Federal do Pampa, 2023)
This project addresses the synergy between Public Relations (PR) and Technical Social Work (TSW), highlighting how the strategic incorporation of TSW by PR professionals can promote socio-economic sustainability and alleviate challenges in vulnerable communities. The proposed guide aims to integrate the practices of both disciplines, offering a flexible and adaptable approach for social projects. Contextual analysis reveals a lack of studies exploring this connection, underscoring the relevance of this research to fill this gap. The guide will be distributed free of charge on the RP course portal at UNIPAMPA in São Borja and, potentially, at the Regional Council of PR. Emphasis is placed on the flexibility of strategies, practical examples, and the importance of adaptation in TSW. Results analysis will be conducted after the guide's approval, considering accessibility via AnyFlip and the provided interactivity. The integration of TSW strengthens not only social responsibility but also serves as a strategic path to enhance the institution's reputation and image, marking an evolution in PR and TSW practices.
Keywords: Relações Públicas; Participação social; Integração social; Comunicação nas organizações; Public relations; Social participation; CNPQ::CIENCIAS SOCIAIS APLICADAS